43.7k views
0 votes
Divide. Show your work.

(6x^4-5x^3+6x^2)/2x^2

User Nbryans
by
5.1k points

1 Answer

2 votes
we can do like we did before, distribute the denominator,


\bf \cfrac{6x^4-5x^3+6x^2}{2x^2}\implies \cfrac{6x^4}{2x^2}-\cfrac{5x^3}{2x^2}+\cfrac{6x^2}{2x^2}\implies \cfrac{6}{2}\cdot \cfrac{x^4}{x^2}-\cfrac{5}{2}\cdot \cfrac{x^3}{x^2}+\cfrac{6}{2}\cdot \cfrac{x^2}{x^2} \\\\\\ 3 x^4x^(-2)-\cfrac{5}{2}x^3x^(-2)+3x^2x^(-2)\implies 3x^(4-2)-\cfrac{5}{2}x^(3-2)+3x^(2-2) \\\\\\ 3x^2-\cfrac{5}{2}x+3x^0\implies 3x^2-\cfrac{5}{2}x+3
User Wescpy
by
5.0k points